2007
DOI: 10.1016/j.physbeh.2007.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral inhibition and glucocorticoid dynamics in a rodent model

Abstract: Behavioral inhibition (i.e. avoidance of unfamiliar) has been linked to significant differences in stress physiology and health. Developing an animal model of this common temperament provides a means to experimentally study the development and physiology of this trait as it relates to stress-related health processes. To elaborate such an animal model, we studied individual rat responses to two novel situations that mimic behavioral inhibition tests for humans (one non-social and one social). We measured indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 62 publications
(100 reference statements)
1
34
1
Order By: Relevance
“…These characteristics resemble a behavioral inhibition profile that has been linked to significant differences in stress physiology and is associated with acute and basal glucocorticoid overproduction (Cavigelli et al, 2007). These findings suggest that the interaction between high anxiety and low exploration traits represent a higher risk to the effects of stress in congruence with the human traits of neuroticism and extraversion, which have been suggested to be predictors of an individual's vulnerability or resilience to develop depression (Lara and Akiskal, 2006).…”
Section: Discussionmentioning
confidence: 74%
“…These characteristics resemble a behavioral inhibition profile that has been linked to significant differences in stress physiology and is associated with acute and basal glucocorticoid overproduction (Cavigelli et al, 2007). These findings suggest that the interaction between high anxiety and low exploration traits represent a higher risk to the effects of stress in congruence with the human traits of neuroticism and extraversion, which have been suggested to be predictors of an individual's vulnerability or resilience to develop depression (Lara and Akiskal, 2006).…”
Section: Discussionmentioning
confidence: 74%
“…In adulthood (PND 68-82), we tested offspring responses to two novel arenas that were designed to reduce anxietyprovoking stimuli such as white light and open space (Cavigelli et al, 2007). The arenas are 120 cm  120 cm with 46-cm high white polypropylene walls and a clear plastic cover.…”
Section: Adult Offspring Responses To Noveltymentioning
confidence: 99%
“…Previously we found that rat (Sprague-Dawley) neophobia/philia, characterized by locomotion in an unfamiliar and protected arena, was related to latency to approach novelty, and was moderately stable from pre-weaning age throughout adulthood, and was reproducible across studies (Cavigelli & McClintock, 2003; Cavigelli et al, 2007; Cavigelli, Ragan, Michael, Kovacsics, & Bruscke, 2009). Neophobic or inhibited males also had greater plasma CORT responses to novelty and stress compared with neophilic or non-inhibited males (Takahashi, 1992; Cavigelli & McClintock, 2003; Veenema, Sijtsma, Koolhaas, & de Kloet, 2005; Cavigelli et al, 2007; Qi et al, 2010; Díaz-Morán et al 2013; c.f.…”
mentioning
confidence: 93%
“…Neophobic or inhibited males also had greater plasma CORT responses to novelty and stress compared with neophilic or non-inhibited males (Takahashi, 1992; Cavigelli & McClintock, 2003; Veenema, Sijtsma, Koolhaas, & de Kloet, 2005; Cavigelli et al, 2007; Qi et al, 2010; Díaz-Morán et al 2013; c.f. Dellu et al 1996).…”
mentioning
confidence: 96%
See 1 more Smart Citation